Association of social isolation with health status among community-dwelling Chinese older adults living with homecare services: a cross-sectional survey in Hong Kong - Eliza Lai-Yi Wong; Eliza Lai-Yi Wong; Hong Qiu; Hong Qiu; Annie Wai-Ling Cheung; Annie Wai-Ling Cheung; Hera Hiu-Wah Leung; Frank Youhua Chen; Eng-Kiong Yeoh; Eng-Kiong Yeoh (Frontiers Media S.A., 2023)
BackgroundDefined as having few social relationships or infrequent social contact with family, friends, and the community, social isolation is a public health crisis. We aimed to evaluate the prevalence of social isolation and explore the association between social isolation and health status among community-dwelling Chinese Older Adults living with homecare services.MethodsThis is a cross-sectional survey with a structured questionnaire conducted among older adults aged ≥60 in the Central Kowloon District of Hong Kong during 2017-2018. Social isolation was assessed by the Lubben Social Network Scale-6 and a score less than 12 was defined as socially isolated. Six aspects of health status including fall risk, cognitive function, depression, activities of daily living (ADL), instrumental activities of daily living (IADL), and functional mobility were measured by standardized instruments. Multi-criteria decision analysis (MCDA) was applied to estimate an index to represent the overall health status of the respondents. Multivariate logistic/linear regression models were applied to examine the associations between social isolation and health status after adjusting the sociodemographic characteristics.ResultsAmong the 1,616 participants included in this analysis, the mean age was 80.9 years, 66.3% were female and 41.4% were identified as socially isolated. Compared with the non-isolated group, the socially isolated group had higher proportions of males, divorced or unmarried, ever smoking and drinking, living alone, and living in public housing without religion. After adjusting for confounders, the odds ratios (OR) comparing the socially isolated vs. non-isolated groups were 2.52 (95%CI: 1.79, 3.56) for high fall risk, 1.51 (1.17, 1.94) for cognitive impairment, and 1.78 (1.31, 2.43) for depression. The socially isolated group increased the odds of abnormal ADL, IADL, and functional mobility by 105-150%, and decreased the overall health score by 5.30 (3.42, 7.18).ConclusionWe demonstrated the association of social isolation with poorer physical function and mental health and overall health status among the community-dwelling Chinese older adults living with homecare services. These findings provided new knowledge about the association of social isolation with both physical and mental function for daily living even for those receiving an integrated homecare service in the community. It implies that an unmet healthcare need existed when comparing the service scope of the current homecare services in the community. It also highlighted the need for targeted prevention and intervention initiatives among community-dwelling old adults to alleviate social isolation for better health and good functioning in the community.